2016
DOI: 10.1136/jclinpath-2016-203625
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the intrinsic apoptotic pathway mediates megakaryocytic hyperplasia in myeloproliferative neoplasms

Abstract: AimsMegakaryocyte expansion in myeloproliferative neoplasms (MPNs) is due to uncontrolled proliferation accompanied by dysregulation of proapoptotic and antiapoptotic mechanisms. Here we have investigated the intrinsic and extrinsic apoptotic pathways of megakaryocytes in human MPNs to further define the mechanisms involved.MethodsThe megakaryocytic expression of proapoptotic caspase-8, caspase-9, Diablo, p53 and antiapoptotic survivin proteins was investigated in bone marrow specimens of the MPNs (n=145) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Several studies described modifications in the expression of molecules that participate in the regulation of intrinsic and extrinsic routes of apoptosis, as well as functional studies that showed resistance to apoptosis, indicating that the deregulation of apoptosis in MPNs is a mechanism involved in the pathophysiology and clinic-hematological outcome of these diseases (19,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies described modifications in the expression of molecules that participate in the regulation of intrinsic and extrinsic routes of apoptosis, as well as functional studies that showed resistance to apoptosis, indicating that the deregulation of apoptosis in MPNs is a mechanism involved in the pathophysiology and clinic-hematological outcome of these diseases (19,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The haematopoietic system is subject to a high cellular turnover rate, which makes it particularly sensitive to disturbance in the apoptosis process (28). Altered control of pro-and anti-apoptotic genes and in the relation with JAK2 or STAT5 signaling routes, seem to lead to myeloaccumulation and myeloproliferation, participating in the pathogenesis of MPNs (19,(29)(30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of BCL-xL induces profound thrombocytopenia by triggered BAK/BAX-mediated mitochondrial damage, caspase activation, and premature death of MKC [39,40]. In MPNs, a concerted effect resulted from antiapoptotic BCL-xL over-expression and proapoptotic BNIP-3 downregulation was clearly documented [41].…”
Section: Key Pcd Players In Bcr-abl1-negative Mpn Entitiesmentioning
confidence: 96%
“…A greater proportion of myeloproliferative MKC express survivin compared to its reciprocal inhibitor, DIABLO. Survivin seems to be the key mediator of the MKC survival signature in the MPNs and might be a potential therapeutic target [41]. Recently, new evidence suggested that survivin may be involved in the evasion of cell death by manipulation of autophagy [49].…”
Section: Key Pcd Players In Bcr-abl1-negative Mpn Entitiesmentioning
confidence: 99%
See 1 more Smart Citation